Potential of Leaves of Eighteen Cultivars of Ficus carica as Antioxidants and Profiling of Phenolic Compounds as an Active Molecules: Antioxidant active compounds isolation from the leaves of Ficus carica (cv. Violette solise - Akhtar, Parul; Yaakob, Zahira; Ahmed, Yunus; Shahinuzzaman, Mohammad; Mar Contreras, MarÃa del (Iranian Journal of Pharmaceutical Sciences, 2019)
Ficus carica is a worldwide important crop. Its different parts such as leaves, stem barks, fruit and roots are used in traditional medicine from ancient age to treat the various diseases. In this research, total phenolic content, antioxidant activity, yield of extract and profiling of phenolic compounds of maturated leaves of different cultivars of F. carica were investigated by using two different extraction processes: ultrasound-assisted extraction (UAE) and maceration. The total phenolic content (TPC) was calculated by using Folin-Ciocalteu assay, while DPPH and ABTS assays were used for analysed the antioxidant capacity. Additionally, liquid chromatography (LC) coupled to mass spectrometry (MS) was used to study the individual phenolic compounds present in leaves. Using DPPH assay, the percentages of inhibition and Trolox equivalent antioxidant capacity were found to vary from 66.19 ± 1.01 to 87.06 ± 0.93 % and 53.67 ± 0.81 to 70.25 ± 0.74 mg TE/g DL, respectively, for extracts obtained by maceration. In the case of ultrasonication extraction, these values ranged from 72.84 ± 1.26 to 92.04 ± 1.24 % and 60.73 ± 0.92 to 74.19 ± 0.99 mg TE/g dry leaves (DL). While ABTS assay the latter parameters were found to vary from 96.61 ± 0.22 to 99.33 ± 0.23 % and 56.81 ± 0.12 to 58.32 ± 0.13 mg TE/g DL for maceration, as well as from 97.82 ± 0.23 to 99.79 ± 0.13 % and 57.48 ± 0.13 to 58.57 ± 0.07 mg TE/g DL for ultrasonication extraction. The total phenolic contents varied between 10.70 ± 0.20 to 21.18 ± 0.68 mg GAE/g DL, and 12.94 ± 0.23 to 23.04 ± 0.30 mg GAE/g DL, respectively for the latter extraction processes. The percentages of yields varied from 7.20 ± 0.20% to 13.05 ± 0.23% and 8.25 ± 0.25% to 15.20 ± 0.20 %, respectively, for maceration and ultrasonication extraction. In conclusion, extracts from leaves of F. carica obtained by UAE process showed the highest antioxidant activity, phenolic contents and extraction yields as compared to maceration process. In comparison amongst the leaves, the ‘Violette solise’ cultivar showed the highest antioxidant activity and contain highest phenolic contents. Finally, the extract of this cultivar contained phenolic acids (dihydroxybenzoic acid di-pentoside, caffeic acid, caffeoylmalic acid, coumaroylmalic acid, ferulic acid malate, and psoralic acid glucoside), C-glycosides flavones, rutin and prenylgenistein.